#TITLE_ALTERNATIVE# - MECCA SUFYANA (NIM 10204039) pembimbing : Wahyu Srigutomo, Ph.D, CANDRA
Self-Potential (SP) prospecting is one of the oldest geoelectrical methods and it is still used in many fields of applied geophysics. Since the SP method is sensitive to primary flows, such as heat flow or fluid flow, it has been used often to detect or monitor hydrothermal systems. The development of quantitative interpretation by means of computational modeling is still needed to provide better interpretation of complex subsurface structure and the problem of crosscoupled flows due to hydrothermal convection. In this modeling of the electrokinetic effects, all that is required is a velocity model, models of the crosscoupling parameters and the electric conductivity. With this velocity field and the physical properties models, the electric-convection current algorithm is used to calculate the electric current sources and the resultant self-potential.